Hyperbaric oxygen therapy and preconditioning for ischemic and hemorrhagic stroke - Hu, Sheng-li (Med Gas Res, 2016)
To date, the therapeutic methods for ischemic and hemorrhagic stroke are still limited. The lack of oxygen supply is critical for brain injury following stroke. Hyperbaric oxygen (HBO), an approach through a process in which patients breathe in 100% pure oxygen at over 101 kPa, has been shown to facilitate oxygen delivery and increase oxygen supply. Hence, HBO possesses the potentials to produce beneficial effects on stroke. Actually, accumulated basic and clinical evidences have demonstrated that HBO therapy and preconditioning could induce neuroprotective functions via different mechanisms. Nevertheless, the lack of clinical translational study limits the application of HBO. More translational studies and clinical trials are needed in the future to develop effective HBO protocols.